Codesigning a patient support portal with health professionals and men with prostate cancer: An action research study. (11th April 2022) - Shemesh, Benjamin; Opie, Jacinta; Tsiamis, Ellie; Ayton, Darshini; Satasivam, Prassannah; Wilton, Paula; Gough, Karla; Lewis, Katrina; O'Brien, Colin; Shub, Max; Pomery, Amanda; Mac Manus, Christopher; et al.
Abstract: Introduction: The supportive care needs of men with prostate cancer (PCa) have been well documented, but little is known about how an online portal may address these. This study sought to determine priority issues facing men with PCa, barriers and enablers to accessing care and whether health professionals (HPs) and men would support the inclusion of a patient‐reported outcome (PRO) comparator tool. Methods: We conducted four online focus groups with HPs recruited from healthcare services in Victoria, followed by seven online codesign workshops with men with PCa, recruited through the Victorian Prostate Cancer Outcomes Registry, Prostate Cancer Foundation Australia and the Cancer Council Victoria. Men were eligible to participate if they had lived experience of PCa and access to the internet. We analysed focus groups thematically. Workshops were analysed using descriptive‐content analysis. Results: HPs ( n = 39) highlighted that men had shifting priorities over time, but noted the importance of providing information to men in lay terms to assist in treatment decision‐making and side‐effect management. HPs identified key enablers to men accessing support services such as practice nurses, partners and having men share their stories with each other. HPs raised financial, cultural, geographic and emotional barriers to accessing supportive care. Inclusion of a PRO comparator tool received mixed support from HPs, with 41% ( n = 16) supportive, 49% ( n = 19) unsure and 10% ( n = 4) not supportive. Men involved in workshops ( n = 28) identified informational needs to assist in treatment decision‐making and side‐effect management as the top priority throughout care. Men described support groups and practice nurses as key enablers. Short consultation times and complex information were described as barriers. Unlike HPs, all men supported the inclusion of a PRO comparator tool in a portal. Conclusions: Our findings suggest that a patient support portal should provide information in lay terms that address the shifting priorities of men with PCa. Men with PCa would welcome the development of a portal to centralize support information and a PRO comparator tool to prompt health‐seeking behaviour. Future research will implement these findings in the development of a portal, and pilot and evaluate the portal within a population‐based sample. Patient or Public Contribution: This project adopted a codesign approach including both men with PCa and HPs involved in PCa care. Men with PCa also formed part of the study's steering committee and consumer advisory groups. HPs were consulted in a serious of online focus groups. Subsequently, men with PCa and their support persons participated in workshops. Men with PCa were also involved in the preparation of this manuscript.